Facility Layout Design Using Activity Relationship Chart and Simulation (Case Study in UKM Bambu Karya Manunggal) - Astuti, Marni (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The current industrial development is required to improve the quality of production by continuing to improve the production process in order to continue to compete in the market, both locally, nationally and internationally. This demand also applies to small and medium industries that have limited capital, labor, land and technology. UKM Karya Manunggal is a small business unit that is engaged in making furniture made from bamboo. Problems of SMEs with available land, most areas are used for placement of work in process and placement of materials that should not be used so that it can disrupt the smooth movement of material movement. Mapping the real conditions of Karya Manunggal UKM by using ProModel software can know the description of material handling, input output from each work station and work in process. The closeness relationship between work stations in the initial conditions compared to using Activity Relationship Chart (ARC), resulted in a distance difference of 90.55 meters or changed by 4.94%. The output of a computer simulation results in a change from one process to another that changes. Initial conditions for raw material operators were 99.4% to 59.2%. The operator of the initial condition pattern was 21.9% to 21.2%. The rattan operator had initial conditions of 7.3% to 4.6%. Operators finish initial conditions 2.7% to 2.3%